Curbing the spread of nuclear weapons. - Bellany, Ian (Manchester University Press, 2006)
Provides a fully detailed but accessible and accurate introduction to the technical aspects of nuclear energy and nuclear weapons Demonstrates that international security is unlikely to benefit from encouraging the spread of nuclear weapons Includes a full discussion of the phenomenon of nuclear-free zones, with particular emphasis on the zone covering Latin America Frankly appraises the International Atomic Energy Agency's safeguards system.